What constitutes a wetland in the New Zealand Coastal Marine Area? – a scientific perspective - Philippe Gerbeaux; Terry M. Hume (New Zealand Journal of Marine and Freshwater Research, 2022)
There is often confusion and sometimes controversy over whether a specific habitat or ecosystem is considered a wetland. In 2021, the New Zealand High Court issued a judgement that the wetland rules in the Resource Management (National Environmental Standards for Freshwater) Regulations 2020 (NES‐F) do apply to wetlands in the Coastal Marine Area (CMA), more particularly which ones apply to ‘natural wetlands’. From a scientific standpoint, the term ‘coastal wetland’ can be applied to all wetland types located in New Zealand coastal hydrosystems, including non‐tidal wetlands influenced, at least in part, by coastal processes. This means coastal wetlands can be found within and outside (although adjacent to) the CMA. In order to map the boundaries of wetlands currently identified within the CMA, their seaward and landward limits can be determined as: ‘areas of marine water, the depth of which, at low tide, does not exceed six metres’, and the ‘CMA definition’, respectively.